Extensive hypertrophic lupus erythematosus: Atypical presentation - Tarun Narang; Meghna Sharma; Nigabh Gulati; Anureet Kaur (Wolters Kluwer Medknow Publications, 2012)
Lupus erythematosus (LE) is a disease with a wide spectrum of cutaneous and systemic manifestations. Clinical features of patients with LE show a great variation, and for this reason it is difficult to develop a unifying concept of this disease. Our objective is to present a case of hypertrophic LE with atypical morphology and extensive involvement, who responded favorably to isotretinoin. Diagnosis of hypertrophic lupus erythematosus (HLE) was confirmed by characteristic histopathological findings. Combination therapy with isotretinoin and hydroxychloroquine resulted in flattening and repression of previously refractory skin lesions. Sometimes, HLE lesions may present a diagnostic and therapeutic dilemma. In long standing lesions, squamous cell carcinoma may arise. Therefore, HLE requires adequate therapy with clinical and histopathological follow up.